Challenges of Energy Renovation - Van der Schoor, Tineke; Sanders, Fred (Urban planning, 2022)
One of the most complex and urgent challenges in the energy transition is the large-scale refurbishment of the existing housing stock in the built environment. In order to comply with the goals of the Paris convention, the aim is to live “energy-neutral,” that is, a dwelling should produce as much sustainable energy as it consumes on a yearly basis. This means that millions of existing houses need to undergo a radical energy retrofit. In the next 30 years, all dwellings should be upgraded to nearly zero-energy buildings, which is a challenge to accomplish for a reasonable price. Across the EU, many projects have developed successful approaches to the improvement of building technologies and processes, as well a better involvement of citizens. It is important to compare and contrast such approaches and disseminate lessons learned. In practice, it is crucial to raise the level of participation of inhabitants in neighborhood renovation activities. Therefore, the central question of this issue is: How can we increase the involvement of tenants and homeowners into this radical energy renovation?